2014
DOI: 10.5505/tjtes.2014.62829
|View full text |Cite
|
Sign up to set email alerts
|

Are neutrophil-lymphocyte ratio and platelet-lymphocyte ratio as effective as Fournier's gangrene severity index for predicting the number of debridements in Fourner's gangrene?

Abstract: BACKGROUND: Fournier's gangrene (FG) is a rapidly progressive and necrotizing infection of the subcutaneous and fascial tissues with a high mortality rate. In the present study, we aimed to investigate prognostic factors and analyze the outcomes of 68 patients in a tertiary reference hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
(41 reference statements)
0
22
1
Order By: Relevance
“…Therefore, several studies have focused on reducing the number of parameters in order to facilitate mortality prediction in FG. 12,13 One such parameter for predicting mortality in FG was assessed by Kahramanca et al 3 , who found that the neutrophil-lymphocyte ratio and platelet-to-lymphocyte ratio were useful for determining FG prognosis. 3 As early and aggressive surgical therapy remains the most effective treatment, we focused on the number of surgical debridements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, several studies have focused on reducing the number of parameters in order to facilitate mortality prediction in FG. 12,13 One such parameter for predicting mortality in FG was assessed by Kahramanca et al 3 , who found that the neutrophil-lymphocyte ratio and platelet-to-lymphocyte ratio were useful for determining FG prognosis. 3 As early and aggressive surgical therapy remains the most effective treatment, we focused on the number of surgical debridements.…”
Section: Discussionmentioning
confidence: 99%
“…Many scoring systems have been proposed for predicting the mortality rate of FG patients, including important indexes such as APACHE II, FGSI, the Laboratory Risk Indicator for Necrotizing Fasciitis and UFGSI. 1,3,5 However, under urgent conditions, it is not always easy to calculate multiple parameters. Therefore, several studies have focused on reducing the number of parameters in order to facilitate mortality prediction in FG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations